Process modelling and optimization of a 250 MW IGCC system: Model setup, validation, and preliminary predictions. (1st June 2023) - Xu, Qilong; Wang, Shuai; Luo, Kun; Mu, Yanfei; Pan, Lu; Fan, Jianren
Abstract: Integrated gasification combined cycle (IGCC) has emerged as a clean and efficient power generation technology, yet a cost-effective tool for process modelling and optimization of industrial-scale IGCC systems is still lacking. Accordingly, this work established an integrated model to predict the efficiency of a 250 MW industrial-scale IGCC system. After comprehensive validations with the design values and experimental data, the integrated model was used to predict power generation of the IGCC system under different load conditions (i.e., 50%, 70%, and 100%), with a focus on the efficiency assessment by energy analysis and exergy analysis. The results show that the IGCC system can operate stably under wide load conditions. Under the full load condition, the total power generation of the IGCC system is 262, 051 kW; The thermal efficiency of the investigated IGCC system is 45.7%, higher than the conventional IGCC systems with energy efficiency in the range of 40%–45%. The exergy analysis considering the energy quality is more reasonable to assess the efficiency of the IGCC system with energy conversion and utilization, with an exergy efficiency of 41.8%. The air separation and gasification units have high energy consumption but low efficiency, which needs to be further optimized to improve system efficiency. Graphical abstract: Image 1 Highlights: Process modelling of a 250 MW industrial-scale IGCC system was conducted. The IGCC model was well-validated with the design values and experimental data. The integrated IGCC model can operate stably under wide load conditions from 50% to 100%. The efficiency of the IGCC system was assessed by energy analysis and exergy analysis. The thermal efficiency of the IGCC system is 45.7% while the exergy efficiency is 41.8%.